Institutional Balancing and International Relations Theory: Economic Interdependence and Balance of Power Strategies in Southeast Asia - He, Kai (European journal of international relations, 2008)
This study integrates elements of neorealist and neoliberal theories with a model of institutional balancing that identifies the conditions under which this form of soft balancing occurs. Institutional balancing, i.e. countering pressures or threats through initiating, utilizing, and dominating multilateral institutions, is a new realist strategy for states to pursue security under anarchy. The interplay between the distribution of capabilities and strong economic interdependence shapes states' decisions on when and how to employ this strategy. Historical examples include: inclusive and exclusive efforts by Third World states and the superpowers to organize voting blocs in the UN during the Cold War; inclusive institutional balancing of ASEAN states to constrain China and ensure US support in the ASEAN Regional Forum (ARF) after the Cold War; exclusive institutional balancing of ASEAN states against the US in the ASEAN Plus Three (APT) summit after the Southeast Asian financial crisis. These examples illustrate the logic of institutional balancing under the conditions of bipolarity, incipient multipolarity, and unipolarity.